Pengaruh Penggunaan Instagram dan TikTok terhadap Peningkatan Penjualan di Beeancashop - Syahvira Bainca Isman; Ahmad Maulidizen (Penerbit Goodwood, 2025)
Purpose: This study investigates which social media platform, Instagram or TikTok, has a greater influence on increasing sales at Beeancashop Methodology/approach: A quantitative research method was employed with 100 respondents. Data was analyzed using SPSS Version 26 to measure the impact of both platforms on sales. Results/findings: The study revealed that Instagram and TikTok together contribute 90.1% to Beeancashop’s sales. While both platforms had a positive influence, TikTok showed a significant effect on sales, whereas Instagram alone did not. Conclusions: The study concludes that Instagram does not have a significant effect on sales at Beeancashop, while TikTok has a significant positive effect. Furthermore, Instagram and TikTok together significantly influence sales, indicating that social media content, particularly on TikTok, plays a key role in driving sales growth at Beeancashop. Limitations: The study only focused on two social media platforms and limited the sample size to 100 respondents, which may not fully represent a broader consumer base. Contribution: This research offers insights into how TikTok plays a more significant role than Instagram in driving sales for a local fashion brand like Beeancashop in Indonesia, emphasizing the need for a targeted social media strategy.